Problematika Rancangan Undang-Undang Perampasan Aset Ditinjau Dari Prespektif Hak Asasi Manusia Dan Keadilan Sosial - Rico Martin (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The Draft Law on Asset Seizure has been the focus of attention in the context of corruption eradication in Indonesia. However, the implementation of this bill raises several implications for human rights (HR) and social justice that need to be seriously considered. This research aims to analyze the implications of the Asset Seizure Bill for HR and social justice in the context of corruption eradication in Indonesia. Through a critical analysis approach, this study explores the positive and negative impacts of the Asset Seizure Bill on HR, including the right to privacy, freedom of speech, and the right to justice In accordance with Article 28G paragraph (1) and Article 28H paragraph (4) of the 1945 Constitution of the Republic of Indonesia. Additionally, this research also discusses the implications of the bill for social justice, including fair asset distribution and protection for vulnerable groups. The results of this study provide insights into the complexity of implementing the Asset Seizure Bill and the importance of ensuring that corruption eradication efforts do not violate HR principles and social justice According to Article 36 paragraph (2) of Human Rights Law No. 39 of 1999.